Correction to: Intervertebral disc penetration by antibiotics used prophylactically in spinal surgery: implications for the current standards and treatment of disc infections - Capoor, Manu N; Lochman, Jan; McDowell, Andrew; Schmitz, Jonathan E; Solansky, Martin; Zapletalova, Martina; Alamin, Todd F; Coscia, Michael F; Garfin, Steven R; Jancalek, Radim; Ruzicka, Filip; Shamie, A Nick; et al. (European spine journal, 2019)
Unfortunately, the complete conflict of interest statement was missed out in the original publication. The same is given below.